Impact of the installed inlet ventilation unit in the window on its overall aerodynamic and thermal properties (2019)
The article deals with the issue of ventilation of modern low-energy buildings, where on the one hand there are hygienic requirements for the required air exchange in the building and on the other hand the requirements of energy efficiency of buildings. A frequently used system in Slovakia in the present is a hybrid vacuum ventilation with air inlet through the ventilation unit situated in the window construction or in the facade construction and with air exhaust through the shaft with exhaust fan. The subject of the article are the supply ventilation units installed in the window construction. On the examples of two particular above window ventilation units, it performs their laboratory experimental aerodynamic quantification, expressed in volumetric air flow depending on the pressure difference, necessary for designing of the ventilation system. The laboratory experiment also assesses the influence of the ventilation unit on the overall thermo-technical properties of the window, expressed by the heat transfer coefficient.